2012
DOI: 10.4103/0970-4388.100003
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations leading to the diagnosis of acute lymphoblastic leukemia in a young girl

Abstract: dentists must be able to clearly recognize oral physiological characteristics, and, when identifying changes of normalcy, to fully investigate it requesting additional tests or referring the patient to specialized professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…15 Hou et al, who examined patients with AL by dividing them into two types (ALL and AML), reported head and neck LAP in patients with ALL more than with AML (71.4% > 45%). 9 There are many case reports in the literature that reported submandibular LAP 6,11,[19][20][21][22][23] and/or cervical LAP 6,11,18,[24][25][26][27] in the head and neck region in AL patients. The relatively lower frequency of LAP in this study compared to previous studies may be related to the inclusion of only newly diagnosed AL patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 Hou et al, who examined patients with AL by dividing them into two types (ALL and AML), reported head and neck LAP in patients with ALL more than with AML (71.4% > 45%). 9 There are many case reports in the literature that reported submandibular LAP 6,11,[19][20][21][22][23] and/or cervical LAP 6,11,18,[24][25][26][27] in the head and neck region in AL patients. The relatively lower frequency of LAP in this study compared to previous studies may be related to the inclusion of only newly diagnosed AL patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies about oral hygiene and periodontal status in adult patients with leukemia during chemotherapy. The literature mainly presents information on the oral health of children [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%